Answer:
![\begin{gathered} f(x)=3(x-(2)/(3))^2-(4)/(3) \\ vertex=((2)/(3),-(4)/(3)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/odvxk7m5qp5hm94umih4crtwdnejfyq5li.png)
Explanations:
Given the quadratic equation expressed as:
![f(x)=3x^2-4x](https://img.qammunity.org/2023/formulas/mathematics/college/ketq04yono2fffkool50z709tzxpivarzi.png)
Factor out 3 from the expression
![f(x)=3(x^2-(4)/(3)x)](https://img.qammunity.org/2023/formulas/mathematics/college/ernhp5oqzlj54tp4woxja00fo4vkypkpp7.png)
Complete the square of the expression in bracket
![\begin{gathered} f(x)=3(x^2-(4)/(3)x+((1)/(2)\cdot(4)/(3))^2-((1)/(2)\cdot(4)/(3))^2) \\ f(x)=3(x^2-(4)/(3)x+((2)/(3))^2-((2)/(3))^2) \\ f(x)=3(x^2-(4)/(3)x+((2)/(3))^2-(4)/(9)) \\ f(x)=3(x-(2)/(3))^2-3((4)/(9)) \\ f(x)=3(x-(2)/(3))^2-(4)/(3) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y6l8a4te4gaz7avrtlo2ndkbb8zcik72uw.png)
Since the vertex form of a quadratic equation is in the form f(x) = a(x-h)^2+k where (h, k) is the vertex.The vertex of the resulting function is (2/3, -4/3)